Markers of vascular damage depending on the blood pressure level: data of the population study ESSE-RF - A. M. Erina; M. A. Boyarinova; E. V. Moguchaya; E. P. Kolesova; A. S. Aliyeva; O. P. Rotar; E. I. Baranova; S. A. Shalnova; A. D. Deev; Z. T. Astakhova; L. Z. Bolieva; G. V. Tolparov; et al. (Российский кардиологический журнал, 2020)
Aim. To evaluate the relationship of prehypertension (preHTN) with vascular wall damage and decreased renal function depending on cardiovascular risk in a representative sample of Russian population.Material and methods. As a part the ESSE-RF study in 4 regions (St. Petersburg, Tomsk, Tyumen, the Republic of North Ossetia), 7042 participants aged 25-64 were additionally examined for state of vessels. All participants signed informed consent and completed the approved questionnaires. Anthropometry, fasting glucose and blood pressure (BP) levels were assessed. BP was measured by the OMRON monitor (Japan) twice on the right hand in a sitting position; average BP was calculated. The optimal BP was considered <120/80 mm Hg, preHTN — 120-139/80-89 mm Hg, HTN — ≥140/90 mm Hg or antihypertensive therapy. The 10-year risk of fatal cardiovascular diseases was determined according to the SCORE charts. Glomerular filtration rate (GFR) was calculated using the CKD-EPI equation. Investigation of vessels was performed using a vascular screening system VaSera, Fukuda Denshi. Cardio-ankle vascular index (CAVI) and ankle-brachial index (ABI) was determined. Statistical analysis was performed using SPSS Statistics 20.Results. The analysis included data of 6906 participants, among which women predominated (n=4531; 65,6%). An increase in the prevalence of subclinical vascular lesion according to CAVI was detected with a BP increase from optimal to preHTN and HTN (0,06, 0,19 and 0,75, respectively). According to ABI, this pattern was not observed (0,24, 0,22 and 0,54, respectively). The prevalence of ABI <0,9 was greatest in the HTN group and did not significantly differ between patients with preHTN and optimal BP. After the exclusion of 1610 patients belonging to the groups of high and very high cardiovascular risk, the prevalence of subclinical vascular lesion was reevaluated. With a BP increase from optimal to preHTN and HTN in the low-risk groups of cardiovascular events, an increase in the prevalence of subclinical vascular lesions was also observed only according to CAVI (0,11, 0,28 and 0,62, respectively). Due to the low prevalence of chronic kidney disease (CKD) in the general population (n=7), the analysis of CKD prevalence in groups by BP level was not carried out. According to linear regression analysis (adjusted for sex, age, body mass index, total cholesterol level), significant associations of systolic BP with GFR, CAVI, and ABI were not detected in the groups of optimal BP, preHTN, and HTN.Conclusion. Regardless of cardiovascular risk grade, an increase in the prevalence of subclinical vascular lesions was detected with an increase in BP from optimal to preHTN and HTN only according to CAVI. The prevalence of decreased ABI did not significantly differ between patients with preHTN and optimal BP. No association of GFR reduction with preHTN has been identified.